Kesehatan Mental, Konsumsi Rokok dengan Status Gizi Remaja Putra SMK Negeri 3 Palu - Dian Mulyanti; Ni Ketut Kariani; Lilik Sofiatus Solikhah (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Adolescents are a vulnerable group facing nutritional problems, therefore nutritional needs are crucial. Unhealthy lifestyle changes, such as excessive cigarette consumption, can lead to nutritional status problems. This study aims to analyze the relationship between mental health and cigarette consumption with the nutritional status of male adolescents at SMK Negeri 3 Palu. This study was quantitative, using a cross-sectional approach with a population of adolescents at SMK Negeri 3 Palu aged 16-18 years. This study was conducted in December 2024. The sample size was 103 individuals, using a stratified random sampling technique. Based on the results of the Spearman rank test, it shows that the adolescents who experience the most mental health problems are at a mild level with a nutritional status of 42.6% (p = 0.724) > value ∝ 0.05 and the adolescents who have the most heavy cigarette consumption with a nutritional status of 48.8% (p = 0.221) > value ∝ 0.05, which means there is no relationship between mental health and nutritional status and there is no relationship between cigarette consumption and the nutritional status of male adolescents at SMK Negeri 3 Palu.